Sewage treatment plants economic evaluation of innovative technologies for energy efficiency - Stamatelatou, Katerina; Tsagarakis, Konstantinos (Integrated environmental technology series, 2015)
Sewage Treatment Plants: Economic Evaluation of Innovative Technologies for Energy Efficiency aims to show how cost saving can be achieved in sewage treatment plants through implementation of novel, energy efficient technologies or modification of the conventional, energy demanding treatment facilities towards the concept of energy streamlining.